An extraordinary experience Prophet Muhammad for little hearts - Khan , S (India, Good words kidz, 2004)
The story begins with the Prophet Muhammad (PBUH) being visited by the angel Jibril (Gabriel), who takes him on a miraculous journey from Makkah to Jerusalem (Isra). From there, the Prophet ascends to the heavens (Miraj), where he meets various prophets and is shown the signs of Allah's creation. This journey culminates in the establishment of the five daily prayers (Salah) as a gift to the Muslim Ummah.